Prevalence of hypothyroidism in patients with biliary stones:a prospective study - Singh, Rana Ranjit; Gupta, Arun; Shah, Sukrit; Shah, Avreen Singh; Ded, Kulwant Singh; Bhatia, Amritpal Singh (International Surgery Journal, 2016)
Background: Biliary stones (gall bladder stones and common bile duct stones) are hardened concretions that develop due to supersaturation of bile. The known risk factors for development of biliary stones include genetics, body weight, high fat diet, diabetes, women taking estrogen containing pills and decreased motility of gall bladder. Of late there has been discussion whether hypothyroidism could lead to formation of biliary stones. Aim of our study is to analyze the prevalance of hypothyroidism in patients of biliary stones and subsequently finding a correlation between hypothyroidism and formation of biliary stones. Methods: The present study was conducted on 100 patients of biliary stones admitted in inpatient department of Surgery at SGRDIMSAR, Amritsar. Their fasting thyroid and lipid profiles were tested to study the prevalence of hypothyroidism in these patients of biliary stones. Results: Percentage of males with gall stones who were diagnosed as hypothyroid, euthyroid and hyperthyroid is 24%, 64% and 12% respectively. Whereas males with common bile duct (CBD) stones who were hypothyroid, euthyroid and hyperthyroid were 18%, 62.5% and 18.75% respectively. Percentage of females with gall stones diagnosed hypothyroid, euthyroid and hyperthyroid was 24.4%, 65.85% and 1% respectively. Percentage of females with common bile duct stones who were hypothyroid, euthyroid and hyperthyroid were 27.7%, 61.1% and 1.1% respectively. Conclusions: We therefore conclude that the role of hypothyroidism with respect to biliary stone formation in human beings is currently not well investigated and further research is needed.